zad1. Zapisz w postaci sumy algebraicznej
a) (2a + b) * c - (2ac - bc + 1)
b) 5(x - z) + 2(z - x)
c) 2x²(x - 5) - 3x(x² - 3x + 5)
d) 6 (a² + b + ⅓) - 6 (a² - ½) - 3 (b + ⅓)



Odpowiedź :

Maja12
a) 2ac+bc-2ac+bc-1=2bc-1
b) 5x-5z+2z-2x=3x-3z
c) 2x³-10x²-3x³-9x²-15x=-x³-19x²-15x
d) 6a²+6b+2-6a²+3-3b-1=3b+4
a)=2ac+bc-2ac+bc-1=2bc-1
b)=5x-5z+2z-2x=3x-3z
c)=2x³-10x²-3x³+9x²-15x=-x³-x²-15x
d)=6a²+6b+2-6a²+3-3b-1=3b-4

prosze powinno być dobrze bo w odp wyniki sie zgadzaja z odp z tyłu ksiązki :P
a) 2ac+bc-2ac+bc-1=2bc-1
b) 5x-5z+2z-2x=3x-3z
c) 2x³-10x²-3x³-9x²-15x=-x³-19x²-15x
d) 6a²+6b+2-6a²+3-3b-1=3b+4